The Influence of Business Type on Social Media Platform Preferences and Digital Marketing Effectiveness - Ahmad Efendi; Sumarsih Sumarsih (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The advancement of digital technology has significantly reshaped marketing practices, with social media emerging as one of the most influential tools for business promotion and customer engagement. In this context, this study sets out to explore how different types of businesses influence the selection of social media platforms, and in turn, how these choices affect the overall effectiveness of digital campaigns. To address this objective, a quantitative survey was conducted involving 350 business actors operating in Makassar. The data were analyzed using multiple regression and mediation analysis, enabling a robust examination of the relationships between business characteristics, platform preferences, and marketing outcomes. The empirical findings suggest that businesses offering visually oriented products such as those in the fashion and culinary sectors tend to select platforms like Instagram, TikTok, and Facebook, given their visual and interactive features that align well with product presentation and consumer appeal. The study emphasizes the strategic importance of achieving a strong fit between business type and platform selection. By doing so, it provides a practical framework that can help MSMEs and other enterprises design more effective and targeted digital marketing strategies, tailored to their internal characteristics and operational needs.